A renewable energy scenario for a new low carbon settlement in northern Italy: Biomass district heating coupled with heat pump and solar photovoltaic system. (1st September 2020) - Aste, Niccolò; Caputo, Paola; Del Pero, Claudio; Ferla, Giulio; Huerto-Cardenas, Harold Enrique; Leonforte, Fabrizio; Miglioli, Alessandro
Abstract: In the framework of the building sector de-carbonization, the case of a new nearly zero-energy district, located in the Milan urban area (Italy), is presented. In particular, the scope of the work is to demonstrate that the proposed energy concept, based on the combination of low-energy building design and high-efficiency technical systems, allows the reduction of the final energy uses. After the evaluation of the energy needs, a low-temperature and small-size wood biomass district thermal plant was designed to be integrated with groundwater heat pumps (GWHP) and solar photovoltaic (PV) systems, taking up the challenge to design an almost full-renewable urban district by means of a Multi-Energy System. The core is a biomass boiler coupled with a small combined heat and power (CHP) unit with a twin-screw steam expander (TSSE). The heat produced by the CHP satisfies a consistent fraction of space heating and domestic hot water (DHW) needs during the winter season. GWHPs coupled with PV satisfy remaining thermal needs in winter and the entire thermal needs in mid-season and in the summer period. The obtained outcomes prove the benefits of the combination of a wood biomass CHP with GWHPs and PV with a significant share of renewable energies. Highlights: Provide an overview of the evolution of district heating networks. Propose a solution for energy decarbonization of new settlements. Show how biomass CHP, PV systems and heat pumps may be successfully integrated. Propose an effective control strategy to enhance local-RES self-consumption.